Pelargonidin activates the AhR and induces CYP1A1 in primary human hepatocytes and human cancer cell lines HepG2 and LS174T - Kamenickova, Alzbeta; Anzenbacherova, Eva; Pavek, Petr; Soshilov, Anatoly A; Denison, Michael S; Anzenbacher, Pavel; Dvorak, Zdenek (Toxicology letters, 2013)
We examined the effects of anthocyanidins (cyanidin, delphinidin, malvidin, peonidin, petunidin, pelargonidin) on the aryl hydrocarbon receptor (AhR)-CYP1A1 signaling pathway in human hepatocytes, hepatic HepG2 and intestinal LS174T cancer cells. AhR-dependent reporter gene expression in transfected HepG2 cells was increased by pelargonidin in a concentration-dependent manner at 24h. Similarly, pelargonidin induced the expression of CYP1A1 mRNA up to 5-fold in HepG2 and LS174T cells relative to the induction by 5 nM 2,3,7,8-tetrachlorodibenzodioxin (TCDD), the most potent activator of AhR. CYP1A1 and CYP1A2 mRNAs were also increased by pelargonidin in three primary human hepatocytes cultures (approximately 5% of TCDD potency) and the increase in CYP1A1 protein in HepG2 and LS174T cells was comparable to the increase in catalytic activity of CYP1A1 enzyme. Ligand binding analysis demonstrated that pelargonidin was a weak ligand of AhR. Enzyme kinetic analyses using human liver microsomes revealed inhibition of CYP1A1 activity by delphinidin (IC50 78 μM) and pelargonidin (IC50 33 μM). Overall, although most anthocyanidins had no effects on AhR-CYP1A1 signaling, pelargonidin can bind to and activate the AhR and AhR-dependent gene expression, and pelargonidin and delphinidin inhibit the CYP1A1 catalytic activity.
Keywords: kinetika; Microsomes, Liver; Liver Neoplasms; messenger RNA; Transcriptional Activation; signální transdukce; Dose-Response Relationship, Drug; Hepatocytes; vztah mezi dávkou a účinkem léčiva; buňky Hep G2; anthokyaniny; Anthocyanins; ligandy; nádory jater; Primary Cell Culture; transfekce; enzymová indukce; Promoter Regions, Genetic; Signal Transduction; Polychlorinated Dibenzodioxins; Receptors, Aryl Hydrocarbon; cytochrom P-450 CYP1A1; primární buněčná kultura; Hep G2 Cells; Enzyme Induction; transkripční faktory bHLH; střevní nádory; hepatocyty; Ligands; RNA, Messenger; Humans; aktivace transkripce; Basic Helix-Loop-Helix Transcription Factors; Kinetics; Transfection; promotorové oblasti (genetika); jaterní mikrozomy; polychlorované dibenzodioxiny; receptory aromatických uhlovodíků; Intestinal Neoplasms; lidé; Cytochrome P-450 CYP1A1